Joint metabolome and transcriptome analysis of the effects of exogenous GA3 on endogenous hormones in sweet cherry and mining of potential regulatory genes - Chen, Chaoqun; Chen, Hongxu; Chen, Yuanfei; Yang, Wenlong; Li, Mengyao; Sun, Bo; Song, Haiyan; Tang, Wenjing; Zhang, Yao; Gong, Ronggao (Frontiers in Plant Science, 2022)
Gibberellin (GA) is an important phytohormone that can participate in various developmental processes of plants. The study found that application of GA3 can induce parthenocarpy fruit and improve fruit set. However, the use of GA3 affects endogenous hormones in fruits, thereby affecting fruit quality. This study mainly investigates the effect of exogenous GA3 on endogenous hormones in sweet cherries. The anabolic pathways of each hormone were analyzed by metabolome and transcriptome to identify key metabolites and genes that affect endogenous hormones in response to exogenous GA3 application. Results showed that exogenous GA3 led to a significant increase in the content of abscisic acid (ABA) and GA and affected jasmonic acid (JA) and auxin (IAA). At the same time, the key structural genes affecting the synthesis of various hormones were preliminarily determined. Combined with transcription factor family analysis, WRKY genes were found to be more sensitive to the use of exogenous GA3, especially the genes belonging to Group III (PaWRKY16, PaWRKY21, PaWRKY38, PaWRKY52, and PaWRKY53). These transcription factors can combine with the promoters of NCED, YUCCA, and other genes to regulate the content of endogenous hormones. These findings lay the foundation for the preliminary determination of the mechanism of GA3’s effect on endogenous hormones in sweet cherry and the biological function of WRKY transcription factors.